TUGAS PROFESIONAL KEPALA MADRASAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN MUTU PENDIDIKAN - Sumarto Sumarto (Pascasarjana IAIN Metro, 2016)
Madrasah is a complex and unique institution. Its complex because Madrasah as organization which has related each other dimension. Madrasah is unique because Madrasah has different character which is in learning process as a place for civilizing of human life. Since that, Madrasah as a organization needs high coordination. Madrasah called success if the head of Madrasah is success. The head of madrasah as supervisor required to monitor, evaluated and guide the whole of Madrasah resources using TEAMWORK principle which have meaning such as Together, Empathy, Asist, Maturity, Willingness, Organization, Respect, and Kindness. Good leadership should have improving the quality of education. Minister of National Education Decision (Mendiknas) Number 162 Year 2003 about Teacher Assignment Guidelines as Principals mention that the head of Madrasah has responsibilities as educator, manager, administrator, supervisor, leader, enterpreneur, and climate creator or can be called as EMASLEC. As a supervisor the head of madrasah help the teacher to solve their difficulties and as the result it can improve their education quality.